Bioaccumulation and health risks of heavy metals associated with consumption of rice grains from croplands in Northern India. Issue 1 (2nd January 2017) - Yadav, Poonam; Singh, Balvinder; Garg, V. K.; Mor, Suman; Pulhani, Vandana
ABSTRACT: The present study focused on micronutrients and nonessential toxic heavy metals quantification and their bio-concentration in soil–rice system in Haryana, India. Composite samples of rice grains and paddy fields' soil were collected, processed and analyzed for heavy metals. Nutrient and heavy metals' content of paddy fields' soil varied over a wide range, having highest Fe content followed by Cu > Cr > Pb > Ni > Zn > Co > Cd. Most of the metals viz. Fe, Zn, Cu and Co found profusely in rice grains were essential micronutrients. Bio-concentration factors (BCFs) in rice grains were in the following order: Zn (0.11) > Co (0.10) > Cu (0.08) = Cr (0.08) > Ni (0.02) > Pb (0.011) > Cd (0.009) > Fe (0.003), indicating higher accumulation of micronutrients than non-essential toxic heavy metals. Principal component analysis revealed three factors accounting for 70% of the total variance which supported correlation among electrical conductivity (EC)-Na, EC-cation exchange capacity (CEC), CEC-Na, pH-TOC, and BCFCu -BCFZn . Health risk indices anticipated that the grains are safe for consumption as non-carcinogenic hazard quotients were less than unity for all the studied heavy metals.